Peran Manajemen Usaha Kecil dalam Pengembangan Usaha Pada Sentra IKM Jawet Pahari Hapakat sebagai Basis Ekonomi Lokal - Rahman Rahman; Fithra Ramadian; Fendy Hariatama H (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2026)
This study aims to analyze the role of small business management in the development of purun craft businesses at the Jawet Pahari Hapakat Integrated IKM Center in Palangka Raya City, identify managerial factors that support and hinder business development, and examine the contribution of small business management to strengthening the center as a sustainable local economic base. This study uses a qualitative approach with a descriptive design. The research subjects consist of craftsmen, center managers, and related parties involved in the management of purun handicraft businesses, with purposive selection of informants to obtain in-depth data. Data collection techniques were carried out through observation, in-depth interviews, and documentation of production, marketing, and business administration activities. Data analysis was conducted using a qualitative descriptive approach through data reduction, data presentation, and verification of findings to obtain a comprehensive understanding of management practices, supporting and inhibiting factors, and the contribution of small business management. The results of the study indicate that integrated planning, organization, implementation, and control support the sustainability and quality improvement of purun craft businesses, while supporting factors such as artisan skills, community collaboration, and the involvement of center managers strengthen management effectiveness. The obstacles faced include technological limitations, simple financial records, limited capital, and seasonal availability of raw materials. This study concludes that effective small business management can optimize local economic potential, strengthen the community base, encourage product innovation, and support social, economic, and environmental sustainability at the Jawet Pahari Hapakat IKM Center.